Physicochemical properties and sensory acceptability of different varieties of coconut water and flesh / Atiq Nabihah Asaad, Fadhilah Jailani and Siti Roha Ab Mutalib - Asaad, Atiq Nabihah; Jailani, Fadhilah; Ab Mutalib, Siti Roha (Universiti Teknologi MARA (UiTM), 2022)
Coconut water is a sweet and refreshing drink obtained directly from the immature coconut and its flesh is smooth with a jelly-like structure. In spite of physicochemical properties of coconut water, its sensory characteristics are not much studied. This study was carried out to evaluate the physicochemical properties and sensory acceptability of different varieties of coconut water and flesh. The varieties of coconut used in this study were tall, dwarf, and hybrid coconut. Firstly, the weight of the coconuts were determined in which the tall variety was the heaviest coconut compared to the others. Tall coconut also showed a significantly higher amount of water volume and weight of coconut flesh. The dwarf coconut water revealed the highest pH (5.48± 0.02) with the lower titratable acidity (0.045±0.01 %). The highest total soluble solid (4.97±0.15 oBrix) was found in tall coconut. The fructose and glucose content of coconut water of all varieties were found in a range of 2.70-3.58% and 2.04-3.24%, respectively. Potassium was the most abundant mineral in all coconut samples in which a larger quantity was found in the water of tall coconut and flesh of the dwarf coconut. The Folin-Ciocalteu method showed that dwarf coconut water (9.07±0.00 mg GAE/100 ml) and hybrid coconut flesh (11.57±0.34 mg GAE/100 g) had higher phenolic content than the others. Hybrid coconut flesh exhibited the lowest crude fat content (18.33±1.22 %) than others. Meanwhile, dwarf and hybrid coconut water were more acceptable and appreciated in taste, sweetness, sourness, and overall acceptability. Although the tall coconut flesh was the least acceptable in taste and texture, all samples' overall acceptability was acceptable. In conclusion, dwarf and hybrid coconut have a big potential to produce high-quality beverages and have a good quality of flesh.